A fotografia como possível suporte reflexivo dos direitos humanos em contextos pós-ditatoriais: um estudo do caso argentino - Repezza, Paula Fernandes (2016)
Between 1976 and 1983, Argentina lived a violent military dictatorship, in which practices of state terrorism resulted in a tragic number of tortures, disappearances and deaths, traumas that still haunt the country nowadays. Among multiple forms of reflect about those painful memories and fight for the construction of a memory that doesn’t neglect or nor make this past an euphemism, photography is highlighted for its extensive use both in people’s intimacies and in the creation of works of art that use it as basis to think about grief, memory, identity and human rights. Among many works produced inside this genre, Buena Memoria, by Marcelo Brodski, stand out for its pioneering, complexity and national and international recognition. This dissertation uses the analysis of this work of art, with focus on the centrality of the photographic and the memory in its construction to reflect on how contemporary works of art may/can be used as reflective basis for the human rights, understood under a cultural perspective, especially in a society in which images attain each time a bigger influence in many the layers of our individual and social reality.